Clinical risk scores and blood biomarkers as predictors of long‐term outcome in patients with community‐acquired pneumonia: a 6‐year prospective follow‐up study. (27th January 2015) - Alan, M.; Grolimund, E.; Kutz, A.; Christ‐Crain, M.; Thomann, R.; Falconnier, C.; Hoess, C.; Henzen, C.; Zimmerli, W.; Mueller, B.; Schuetz, P.; the ProHOSP study group
Abstract Objective Prediction of long‐term outcomes in patients with community‐acquired pneumonia (CAP) is incompletely understood. We investigated the value of clinical risk scores [pneumonia severity index (PSI) and CURB‐65] (Confusion, Urea, Respiratory rate, Blood Pressure, Age >65 years) and blood biomarkers of different physiopathological pathways in predicting long‐term survival in a well‐characterized cohort of patients with CAP enrolled in an antibiotic stewardship trial. Design, setting and subjects Patients admitted with CAP to six medical centres in Switzerland were prospectively followed for 6 years. Cox regression models and area under the receiver operating characteristics curve (AUC) were used to investigate associations between initial risk assessment and all‐cause mortality. Main outcome measure All‐cause mortality during a 6‐year follow‐up period. Results Six‐year mortality in the present cohort (median age 73 years) was 45.1% [95% confidence interval (CI) 41.8–48.3%]. Initial PSI and CURB‐65 scores both had excellent long‐term prognostic accuracy, with a stepwise increase in mortality per risk class. The hazard ratios (95% CI) of the highest PSI and CURB‐65 classes (reference: lowest class) were 38.0 (14.0–103.0) and 7.8 (2.2–14.5), respectively, after 6 years. The addition of inflammatory (pro‐adrenomedullin) and cardiac (pro‐atrial natriuretic peptide) blood biomarkers measured upon hospital admission further improved the prognostic capabilities of the PSI (AUC increase from 0.79 to 0.83; P < 0.0001) and the CURB‐65 score (AUC increase from 0.73 to 0.80; P < 0.001). Conclusion Risk assessment using clinical scores allowed accurate long‐term prognostication, which was further improved by the addition of two inflammatory (pro‐adrenomedullin) and cardiac (pro‐atrial natriuretic peptide) blood biomarkers. These data provide a rationale for a more risk‐adapted, 'personalized' strategy for long‐term management of patients with CAP.